Detection and mitigation of pulse-delay attacks in pairwise-secured wireless sensor networks. (2018) - Dargahi, Tooska; Javadi, Hamid H.S.; Shafie, Hosein; Mousavi, Payam
With the advances in technology, there has been an increasing interest in the use of wireless sensor networks (WSNs). WSNs are vulnerable to a wide class of attacks among which pulse-delay attack puts severe threats to the dependability of such networks. This paper proposes a distributed approach to detect and mitigate such attacks in pairwise-secured WSNs. It provides a lower bound on the radio range under which the distributed approach can be performed. Our simulation experiments validate the correctness and efficiency of the proposed approach.